Meningkatkan Kemampuan Peserta Didik Dalam Menentukan Generic Structure Dari Sebuah Teks Report Melalui Metode TAI Pada Kelas IX SMP Negeri 13 Langsa Tahun Pelajaran 2020/2021 - Sulistriana, Merry (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The aims of this research are: 1). to describe the effect of applying the TAI (Team Assisted Individually) method to increasing Student Ability in Determining the Generic Structure of a Report in class IX students of SMP Negeri 13 Langsa in the 2020/2021 academic year. The subjects in the study were 20 students in class IX at SMP Negeri 13 Langsa. Data collection methods used are observation, interviews and documentation. Meanwhile, to test the validity of the data is to use data triangulation. The results of the study show that there is an effect of the application of the TAI (Team Assisted Individually) method on increasing the Ability of Students in Determining the Generic Structure of a Report in class IX students of SMP Negeri 13 Langsa in the 2020/2021 academic year. This can be seen from the results obtained where in the first cycle the student learning outcomes were 60 and after carrying out learning with the TAI method the results obtained were 81.25 in cycle II. With these results, it has been shown that the existence of learning with the TAI method has had a positive impact on improving student learning outcomes. Having these results, in the initial conditions to cycle I the increase was not maximized and after being carried out in cycle II the results obtained increased significantly.